Program Keluarga Harapan: a conditional cash transfer to increase prenatal visits and birth weight - Ratna Frenty Nurkhalim; Indah Susilowati; Krisnita Dwi Jayanti (Journal of Public Health in Africa, 2022)
Conditional Cash Transfer, known as Program Keluarga Harapan (PKH) in Indonesia, is a program that aims to increase maternal and child health. Women benefit directly from the improved obstetrical and reproductive health care and health information that form an integral part of the program. Many studies show the positive impact of conditional cash transfer on improving prenatal visits and birth weight. The objective of the research was to document the impact of Indonesia’s conditional cash transfers (PKH) on prenatal visits and birth weight. We carried out a retrospective cohort study to assess the number of prenatal visits and birth weights among PKH beneficiaries. The data were collected through the KIA books belonging to 184 participants who gave birth between 2012−2017. The results indicate that the mean birth weight among PKH beneficiaries was slightly lower (23.7 g) compared to non-beneficiaries. The PKH program improved prenatal visits for women, but both beneficiaries and non-beneficiaries mostly had already made 8-9 times prenatal visits during their pregnancy. In other words, women in this community were already aware of the importance of prenatal visits even before the program. Incomplete data was the main obstacle to comparing the 6, 12, and 24-month-old babies’ weights. This finding is irrelevant to other conditional cash transfer programs implemented which showed a significant effect of CCT on birth weight.